Comparison of the Effect of Fenugreek and Metformin on Clinical and Metabolic Status of Cases with Polycystic Ovary Syndrome: A Randomized Trial - Sh Mirgalobayat; A Akbari Sene; F Jayervand; M Vazirian; A Mohazzab; M Kazerooni (JRI, 2024)
Background: It is hypothesized that fenugreek seeds are a rich source of fiber with anti-diabetic effects, which can help to lower blood glucose in patients with polycystic ovary syndrome (PCOS). In this study, the clinical and metabolic effects of fenugreek were compared to those of metformin in women with PCOS aged 16-40 years. Methods: In a randomized, triple-blind, parallel clinical trial, the efficacy of fenugreek 333 mg (n=55) was compared with metformin 500 mg (n=55), both administered three times a day in women with PCOS of reproductive age. Changes in some clinical outcomes and metabolic laboratory profile outcomes were evaluated at baseline and two months after the study. Results: By the end of the intervention period, all investigated factors improved significantly in patients of both groups (p<0.05). Reduction in biometric indices (body mass index and waist–hip ratio), fasting blood sugar (FBS), and insulin resistance was significantly higher after metformin consumption (p<0.001). Metformin also significantly improved irregular menstruation (p=0.02). In contrast, fenugreek significantly improved patients' lipid profiles, including low-density lipoprotein (LDL), high-density lipoprotein (HDL), and triglyceride (TG) compared to metformin (p<0.001). Both interventions improved the patient's hair loss and hirsutism. Conclusion: Fenugreek cannot substitute metformin in PCOS treatment. However, regarding its lipid-lowering ability and low frequency of adverse effects, it can be used as an adjuvant treatment in PCOS, especially in PCOS patients with hyperlipidemia and severe hair loss.